HUBUNGAN PERSEPSI SISWA TERHADAP MATA PELAJARAN MATEMATIKA MINAT BELAJAR DAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR MATEMATIKA - Fitri Mustika Sari; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to know the positive and significant relation between students' perception of mathematics , interest in learning mathematics and autonomy in learning mathematics individually or grups with the students’ achievement in learnig mathematics of the X grade students even semester at SMA N 1 Kretek academic year 2013/2014.The type of the study is quantitatif with ex-post-fakco method which means after the occurance with the subjects of study were the student of grade X even semester of SMA N 1 Kretek in academic year 2013/2014. The number of the student was 75. The research instrument testing used simple regression analysis and partial correlation testing. The result of the study showed that there was significant and positive relation between students’ perseption mathematics learning, students’ interest in learning mathematics and autonomy in learning mathematics with the student’ mathematics achievement, seen from the value of tobs ≥ ttable, whilein geup it was show by the partial correlation R=0,4797 with the Fobs=7,075 ≥ Ftable=2,734